2015
DOI: 10.1016/j.molcel.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Addicted to AA (Acetoacetate): A Point of Convergence between Metabolism and BRAF Signaling

Abstract: In this issue Kang et al. (2015) show that oncogenic BRAF(V600E) stimulates expression of ketogenic enzyme 3-hydroxy-3-methylglutaryl-CoA lyase and promotes the formation of the ketone body acetoacetate, which subsequently enhances BRAF(V600E)/MEK/ERK signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…For example, BRAF V600E upregulates the ketogenic enzyme 3-hydroxy-3-methylglutaryl-CoA lyase (HMGCL) in human primary melanoma and hairy cell leukemia cells, and inhibition of HMGCL attenuates cell growth [37]. Acetoacetate, the product of HMGCL, specifically enhances the binding of BRAF V600E to MEK1 to promote MEK-ERK signaling [38].…”
Section: Cancer As a Metabolic Disease: The Role Of Oncogenesmentioning
confidence: 99%
“…For example, BRAF V600E upregulates the ketogenic enzyme 3-hydroxy-3-methylglutaryl-CoA lyase (HMGCL) in human primary melanoma and hairy cell leukemia cells, and inhibition of HMGCL attenuates cell growth [37]. Acetoacetate, the product of HMGCL, specifically enhances the binding of BRAF V600E to MEK1 to promote MEK-ERK signaling [38].…”
Section: Cancer As a Metabolic Disease: The Role Of Oncogenesmentioning
confidence: 99%
“…To determine the molecular identities for members of this ion list (Table S2, m / z = 100), we prepared lipid extracts from HEK-V600E and wt cell lines (as a ground truth and controlled testbed) and subjected the extracts thereof to UPLC-MS/MS, as utilized previously to characterize the biomarker ions identified with PIRL-MS. , Molecular identities for 30 m / z candidates were established (Table ). This list, comprised of several metabolic lipids including phosphatidylethanolamines, phosphatidylcholines, and ceramides among others, adds to the body of knowledge that has documented the effect of BRAF mutations on cellular phenome where metabolic rewiring provides a link between BRAF-MK1 signaling and ketogenesis, consistent with the documented role of acetoacetate in BRAF signaling . Further rationalization of the role of each of the identified lipids in the BRAF metabolic pathway is beyond the scope of this paper and will be revisited in follow-on human tissue studies.…”
Section: Resultsmentioning
confidence: 87%
“…In organs other than the liver, BDH2 dehydrates β-hydroxybutyric acid to form one of the endogenous ketone body molecules, acetoacetate, 9 considered to be a nutritional source for tumours carrying the V600E mutant form of BRAF protooncogene. 33,34 Interestingly, ketone bodies also reduce the growth of pancreatic cancer and cause apoptosis. 35 We found that restoring the expression of BDH2 in NPC cells increased the intracellular acetoacetate level.…”
Section: Discussionmentioning
confidence: 99%
“…38 In recent years, numerous disorders, such as cancer and neurodegenerative diseases, have been linked to deregulated iron homoeostasis. 33,34 Cellular iron metabolism of iron includes three major processes: iron uptake, storage and export of iron. Iron carrier proteins, such as transferrin receptors in glioblastoma and ferritin in serum, were upregulated, thereby increasing iron uptake.…”
Section: Discussionmentioning
confidence: 99%